(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This study examines the ontological and psychological foundations of the relationship between the creative personality and the external environment, focusing on the dialectical tension between individual freedom and social determination. The research problem lies in the insufficient conceptualization of how creative identity emerges through the interaction of internal existential impulses and external socio-cultural constraints. The aim of the study is to develop a theoretical model explaining the formation of creative personality as a dynamic process shaped by contradiction, conflict, and self-transcendence. The research is based on an integrative methodology combining existential philosophy, psychological analysis, and hermeneutic interpretation of literary representations. The findings demonstrate that creative personality is not a stable entity but a continuously evolving structure formed within the tension between autonomy and necessity. The study introduces a dialectical model of creative existence that redefines the role of environment not as a limiting factor but as a constitutive condition of creativity.